Foreign bodies in children's lower urinary tract: A case series and literature review - Kuang, Tongshuai; Cai, Wei; Qian, Weite; Lin, Xiaokun (Frontiers in Pediatrics, 2023)
Background: Children with foreign bodies (FBs) in the lower urinary tract have rarely been reported, and their management remains challenging. This study aimed to describe the characteristics and treatment of FBs in children's lower urinary tract. Methods: We retrospectively analyzed the clinical data on lower urinary tract FBs that were removed in our hospital from August 2017 to August 2022, including demographics, location, symptoms, imaging examinations, and treatment. Results: Four male patients were enrolled, whose ages ranged from 9 to 13 years, with a mean age of 11 years. The course of the disease ranged from 3 h to 2 weeks. Their imaging characteristics were reviewed and analyzed, and two FBs were located in the bladder and two in the urethra. Mosquito forceps were used to remove an acne needle through the urethra in one case. Cystoscopy was first attempted in three cases, in only one of which was the FB removed successfully under endoscopic minimally invasive surgery. In the remaining two cases, removal via transurethral cystoscopy failed, whereby leading to cystotomy being performed. The FBs comprise a skipping rope, hairpin, magnetic bead, and acne needle. The postoperative recovery was uneventful, and no complications occurred during the follow-up period of 3 to 6 months. Conclusion: It is rare for children to have FBs in the lower urinary tract. An early diagnosis, as well as appropriate management of lower urinary tract FBs, can significantly reduce complications. Surgical removal of lower urinary tract FBs can be safe and effective, and relatively better outcomes can be achieved.